下顎歯肉癌頸部転移症例の鎖骨下動脈出血に対してカバードステントを使用した1例 - 加藤, 伸; 佐藤, 豊彦; 池内, 忍; 高森, 康次; 塚本, 浩; 宮下, 英高 (日本口腔外科学会雑誌, 2010)
Sudden hemorrhage is a serious complication related to local recurrence of oral cancer and cervical lymph node metastasis. Massive hemorrhage may lead to fatal outcomes. Even when blood loss is small, persistent hemorrhage may reduce the patient's quality of life. In most cases, it is difficult to select a hemostatic procedure after surgery or radiotherapy. On the other hand, recent advances in intravascular treatment have facilitated various minimally invasive therapies. We report a case of subclavian artery hemorrhage caused by invasion of cervical lymph node metastasis in which hemostasis was achieved with a covered stent using Seldinger's method. A 66-year-old woman with mandibular gingival pain was referred to our hospital. After the histopathological diagnosis of squamous cell carcinoma, surgery and radiotherapy were performed. Recurrence in the supraclavicular fossa was detected 7 months after secondary neck dissection. Although sudden hemorrhage from the site was treated by surgical hemostasis under local anesthesia, recurrent hemorrhage occurred repeatedly. Angiography revealed hemorrhage from the subclavian artery. Placement of a covered stent into the artery was intravascularly performed to achieve hemostasis because surgical procedures were of limited value. Angiography after stent placement confirmed the disappearance of irregular contrast medium leakage. This hemostatic procedure with a covered stent was considered useful for the management of hemorrhage from deep vessels.